2007
DOI: 10.1093/carcin/bgl254
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid induces proteasome-dependent degradation of  -catenin, down-regulation of survivin and apoptosis in human colorectal cancer cells not expressing COX-2

Abstract: n-3 Polyunsaturated fatty acids have been shown to powerfully inhibit the growth of colon cancer cells, mainly acting as pro-apoptotic agents through inhibition of cycloxygenase-2 (COX-2) expression. Since dysregulation of beta-catenin expression is frequently found at early stage of colorectal carcinogenesis, we analyzed whether docosahexaenoic acid (DHA) may modify the expression of beta-catenin in colon cancer cells (SW480 and HCT116) over-expressing this protein, but lacking COX-2. Futhermore, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 47 publications
(67 reference statements)
10
73
0
Order By: Relevance
“…Several studies have suggested that DHA exerts anticancer effects by inducing apoptotic cell death, and several signaling pathways have been reported to be involved in this process [30,31]. In the present study, we report for the first time that DHA-induced apoptosis in human EGFR mutant NSCLC is associated with the ability of DHA to trigger SIRT6 activation, which results in downregulation of Hh signaling ( Figure 6).…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have suggested that DHA exerts anticancer effects by inducing apoptotic cell death, and several signaling pathways have been reported to be involved in this process [30,31]. In the present study, we report for the first time that DHA-induced apoptosis in human EGFR mutant NSCLC is associated with the ability of DHA to trigger SIRT6 activation, which results in downregulation of Hh signaling ( Figure 6).…”
Section: Discussionsupporting
confidence: 57%
“…A previous study in Japan documented that the mean concentration of serum DHA in healthy controls was 18.52 mg/dl (563.0 µM) (17) and previous studies investigating the anti-tumor effects of DHA on colon (18), breast (19) and prostate cancer cells in vivo (20) have used DHA concentrations between 10 and 200 µM. Therefore, the present study used DHA concentrations ≤100 µM to obtain clinically relevant results.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, studies aiming to identify a novel therapeutic agent to treat patients with metastatic RCC are required. The present study used in vitro techniques including MTS and proliferation assays and flow cytometry analysis to investigate the anti-tumor activities of DHA on the proliferative and invasive capacities of RCC cells at clinically relevant concentrations of 10-200 µM, as previously determined (17)(18)(19)(20) Cell proliferation was assessed by counting cell numbers after cells seeded into 6-well plates (1x10 4 cells/well) had been incubated at 37˚C with DHA (0, 50, 100 µM) for 0, 24, 48 and 72 h. The medium used for Caki-1 cells was 1X MEM with 10% FBS and the medium for 786-O cells was RPMI medium 1640 with 10% FBS, as previously stated. Total cell numbers were then counted in four fields using a hemocytometer and mean values were calculated from three replicates.…”
Section: Introductionmentioning
confidence: 99%
“…32 ). Both EPA and DHA decreased the growth of colon tumours in nude mice by reducing vascular endothelial growth factor (VEGF) and COX-2 expression through inhibition of ERK1/2 phosphorylation and hypoxia-induced factor (HIF)-1 α protein expression 108 . Taken together, these results confirm that dietary fat composition alters the molecular portrait of gene expression profiles in colonic epithelium at both initiation and promotion stages of colon carcinogenesis and indicate that these chemopreventive effects are due to direct action of n-3 PUFAs.…”
Section: Regulation Of Specific Transcription Factors and Dha Effectsmentioning
confidence: 99%